Application of QUECHERS Extraction Coupled With GC/MS for Detection of Polycyclic Aromatic Hydrocarbons and Organochloride Pesticides in Lake Water - GBAGUIDI, Magloire Nonvignon Acakpo; YOUSSAO ABDOU KARIM, ALASSANE; Saizonou, Mickael Vitus Martin Kpessou; SINGBO, Romain A. O; DOVONON, LÉONCE FIRMIN COMLAN; ZANNOU, Aimé; SOCLO, HOUÉNOUKPO HENRI; SOCLO, HOUÉNOUKPO HENRI; MAMA, DAOUDA (My University, 2018)
The extensive development of industries gives birth to many chemicals which brings contaminations towards environment. The present study is to apply QUECHERS extraction coupled with GC/MS for detection of polycyclic aromatic hydrocarbons (PAHs) and organochloride pesticides (OCPs) in Lake Nokoué of Benin Republic. The method was first benchmarked with standard PAHs and OCPs, and limit of detection (2-194 ppb) and limit of quantification (8-645 ppb) were obtained with recovery rate of 91-110%. The method was then applied to the detection of PAHs and OCPs in the lake water, no benzo[a]pyrene, chrysene or pyrene was detected. The main origin of PAH compounds in Nokoué Lagoon are material combustion and fuels for Polycyclic Aromatic hydrocarbons and due to remoteness pollution for organochorid pesticides compounds.
Keywords: development; analytical method; research; PAHs; OCPs; QUECHERS GC/MS